Effect of Phacoemulsification Subtype on the Efficacy of Previously Performed Glaucoma Surgery - N. Yu. Yusef; G. V. Voronin; M. K. Bersunkaev; A. V. Volzhanin (Oftalʹmologiâ)
Purpose: to compare the efficacy of existing glaucoma surgery after phacoemulsification (PE) and femtosecond PE (femtoPE).Patients and methods. Study included 30 patients (30 eyes) who have undergone a non-penetrative glaucoma surgery with Burrato II cataract. Patients were evenly distributed to the PE and femtoPE groups. Cataract surgery was performed from 3 months to 1 year after glaucoma surgery. Intraocular pressure (IOP) was evaluated before surgery, on week 1, months 1, 3, and 6.Results. Baseline IOP was comparable in both groups: 17,5 ± 1,3 mmHg in a PE group and 17,9 ± 1,5 mmHg in a femtoPE group. In a PE group a statistically significant IOP increase happened on week 1 and month 1, in a femtoPE group it happened only on week 1. In comparison to the femtoPE group, the PE group was associated with bigger IOP increase after 1 week and 1 month (week 1: 17,0 ± 3,6 and 13,2 ± 1,9 mmHg, respectively; month 1: 13,5 ± 2,2 and 13,0 ± 0,7 mmHg, respectively). In months 3 and 6, there was no intergroup difference (12,2 ± 2,1 and 12,5 ± 1,6 mmHg, respectively; 13,3 ± 1,0 and 12,1 ± 1,8 mmHg, respectively). In all follow-up terms amount of hypotensive eyedrops was bigger in the PE group.Conclusion. FemtoPE is safer than PE in eyes with previous glaucoma surgery. Such eyes are more likely to require hypotensive therapy after PE, rather than after femtoPE, for IOP compensation.